Patterns of asthma medication use: early asthma therapy initiation and asthma outcomes at age 8. - Koster, E.S.; Wijga, A.H.; Zuidgeest, M.G.P.; Belitser, S.V.; Raaijmakers, J.A.; Koppelman, G.H.; Postma, D.S.; Brunekreef, B.; de Jongste, J.C.; Maitland-van der Zee, A.H. (John Wiley and Sons Ltd, 2010)
Wheeze has many underlying pathophysiologies in childhood, but is the main reason for anti-asthma drugs prescription. This study was conducted to describe asthma medication use patterns among children in their first eight years of life. Longitudinal medication use data from 777 children participating in the PIAMA study were used. Medication patterns were described for four groups that started therapy before the third birthday, when the peak in prescriptions occurred in our cohort; short-acting β-agonists (SABA), inhaled corticosteroids (ICS), SABA + ICS or none of these. One third (n = 255) of the children received a first SABA or ICS prescription before age 8. Only three children (1.2%) used medication continuously during follow-up. Of the children who started SABA, 53.8% discontinued within 1-2 years. Of the children who started ICS before age 3, 42.1% discontinued within 1-2 years and 31.6% received additional SABA. 41.5% of the children who started SABA + ICS used this short-term (≤1 -2 years) and 21.5% long-term (≥ 3 years). Fifteen percent of children who did not start asthma therapy in their first 3 years of life did receive prescriptions between age 3 and 8. Children prescribed SABA + ICS before age 3 had the highest prevalence of hyper responsiveness at age 8, and similar prevalence of atopy as the other groups. Asthma medication is prescribed frequently in the first 8 years of life, particularly before age 3, and only few children use it continuously. ICS and SABA prescription occurs especially in those who were more likely to develop signs of asthma at age 8.
Keywords: Epidemiology; Farmacie(FARM); Biomedische technologie en medicijnen; Ziekenhuisstructuur en organisatie van de gezondheidszorg; Public Health; SDG 3 - Good Health and Well-being